Emotional dysregulation in substance use disorders and role and responsibilities of nurses - Baysan Arabacı, Leyla; Ayakdaş Dağlı, Dilek; Taş, Gülsenay (Journal of Dependence, 2018)
Emotions have an important role to starting, using, maintenance and terminating of substance use. Individuals may tend to use substance to reduce stress, to relax, to control anxiety, or to change their feelings. Especially, individuals who have difficulty in regulating emotion can not cope with their negative emotions, often have difficulties in controlling impulses and orienting towards goal-oriented behaviors. For individuals who uses substance initially manage a critical state or crisis, eventually becomes uncontrollable, and the individual finds itself in a vicious circle. This ensures the continuity of substance dependence. At this point, this review has been written to draw attention to the role and responsibilities of nurses in managing emotional regulation, which is one of the important determinants of relapses in dependent individuals, as it is thought that emotional regulation is effective in preventing substance dependency.
Keywords: emotional dysregulation; substance abuse; nurse